Effect of bispectral index-guided anesthesia on consumption of anesthetics and early postoperative cognitive dysfunction after liver transplantation: An observational study. Issue 35 (September 2017) - Cao, Ying-Hao; Chi, Ping; Zhao, Yan-Xing; Dong, Xi-Chen
Abstract : Abstract: The objective of this study was to summarize the incidence of postoperative cognitive dysfunction (POCD) after 7days following liver transplantation (LT), and to evaluate the effectiveness of bispectral index (BIS) guided anesthetic intervention in reducing POCD. Additional serum concentrations of S100β and neuron-specific enolase (NSE) were detected during surgery to determine whether they were reliable predictors of POCD. Patients who underwent LT at Beijing YouAn Hospital Affiliated to Capital University of Medical Science from January 2014 to December 2015 were enrolled. BIS monitor was needed during surgery. Patients who underwent LT without BIS monitoring during August 2012 to December 2014 served as historical controls. A battery of 5 neuropsychological tests were performed and scored preoperatively and 7days after surgery. POCD was diagnosed by the method of one standard deviation (SD). The blood samples of BIS group were collected at 5 time points: just before induction of general anesthesia (T0), 60 minutes after skin incision (T1), 30 minutes after the start of the anhepatic phase (T2), 15 minutes after reperfusion of the new liver (T3), and at 24 hours after surgery (T4). A total of 33 patients were included in BIS group, and 27 in the control group. Mean arterial pressure was different between 2 groups at 30 minutes after the start of the anhepatic phase ( P = .032). The dose of propofol using at anhepatic phase 30 min and new liver 15 min was lower in the BIS group than control group (0.042 ± 0.021 vs. 0.069 ± 0.030, P < .001; 0.053 ± 0.022 vs. 0.072 ± 0.020, P = .001). Five patients were diagnosed as having POCD after 7 days in the BIS group and the incidence of POCD was 15.15%. In the control group, 9 patients had POCD and the incidence of POCD was 33.33%. The incidence of POCD between 2 groups had no statistical difference ( P = .089). S100β increased at stage of anhepatic 30 minutes (T2) and new liver 15 minutes (T3) compared with the stage of before anesthesia (T0) (1.49 ± 0.66 vs. 0.72 ± 0.53, P < .001; 1.92 ± 0.78 vs. 0.72 ± 0.53, P < .001). NSE increased at stage of anhepatic 30 minutes (T2) and new liver 15 minutes (T3) compared with the stage of before anesthesia (T0) (5.80 ± 3.03 vs. 3.58 ± 3.24, P = .001; 10.04 ± 5.65 vs. 3.58 ± 3.24, P < .001). At 24 hours after surgery, S100β had no difference compared to one before anesthesia (1.0 ± 0.62 vs. 0.72 ± 0.53, P = .075), but NSE still remained high (5.19 ± 3.64 vs. 3.58 ± 3.24, P = .043). There were no significant differences in the serum concentrations of S100β between patients with and without POCD at 5 time points of operation ( P > .05). But at 24 hours after surgery, NSE concentrations were still high of patients with POCD (8.14 ± 3.25 vs. 4.81 ± 3.50, P = .035). BIS-guided anesthesia can reduce consumption of propofol during anhepatic and new liver phase. Patients in BIS group seem to have a mild lower incidence of POCD compared to controls, but no statistical significant. The influence of BIS-guided anesthesia on POCD needs to be further confirmed by large-scale clinical study. S100β protein and NSE are well correlative with neural injury, but NSE is more suitable for assessment of incidence of postoperative cognitive deficits after surgery.